PENGARUH PEMAHAMAN, KUALITAS PELAYANAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WP PELAKU UMKM SESUDAH PENERAPAN PP NO.46 TAHUN 2013 (Survey Kantor Pelayanan Pajak Pratama Wonosari ) - Suyanto Suyanto; Diana Alim Kholifah (Jurnal Akuntansi, 2015)
This study was conducted to examine the effect of omprehension, quality of service, and tax penalties to the level of i taxpayer compliance UMKM in KPP Pratama Wonosari. While this study was conducted to examine the effect of comprehension, quality of service, and tax penalties simultaneousuly level of taxpayer compliance UMKM in KPP Pratama Wonosari . This study uses the dependent variable is tax compliance while independent variable are of comprehension, quality of service, and tax penalties. The sampling technique that is taken sksidental sampling. Aksidental sampling is technique determination sample based spontaneity factor, meaning anyone inadertently meet with investigators and accordance with characteristics (traits) than that person is used as s sample. This study classified in quantitative research. Data collection procedures using a question are wich was distributed to the public filled by an taxpayer. While data analys techniques using multiple regression analysis bye the F-test, koefisien determine R2, and T-test. Quality data test of validitas test and reliability test. The clasical assumption test of normaliy test, multicollinearity test, and heteroscedasticity test. The result showed the Comprehension and quality of services significant positive effect on the level of compliance of taxpayer. While tax penalties not significant effect on the level of compliance of taxpayer. And simultaneousulycomprehension, quality of service, and tax penaltiessignificant positive effect on the level of compliance of taxpayer. Results of determination (R2) that show the influence of the kepauhan 70.7% and the remaining 29.3% is influenced by other factors. Keywords: comprehension, quality of service, tax penalties, compliance